Clinical Experience of Non-Invasive Prenatal Chromosomal Aneuploidy Testing in 190,277 Patient Samples - Hu, H.; Liu, H.; Peng, C.; Deng, T.; Fu, X.; Chung, C.; Zhang, E.; Lu, C.; Zhang, K.; Liang, Z.; Yang, Y. (Current Molecular Medicine, 2016)
Objectives: To detect trisomy 21, 18, and 13 in 190,277 clinical samples from the medical diagnostic laboratories of ten hospitals. Methods: The study assessed the clinical performance of non-invasive prenatal testing (NIPT) in detecting trisomy 21, 18, and 13 in 190,277 clinical samples using semiconductor sequencing technology. Results: NIPT participants were at a mean gestation of 17.79 weeks (range, 9–36) and age of 31.12 years (range, 18–46) at the time of testing on average. There were 1,543 (0.81%) positive cases, including 1050 for trisomy 21, 316 for trisomy 18, and 177 for trisomy, 13. The overall sensitivity and specificity for detecting trisomy 21, 18 and 13 combined were 99.61% and 99.91% respectively, and the overall positive predictive value and negative predictive value (PPV and NPV) were 89.74% and 99.99%, respectively. Conclusions: This was the first large clinical study for semiconductor sequencing technologies in NIPT application. Our findings indicate that NIPT has the potential to replace serum biochemistry screening and could be performed at the early gestational age of 9 12 weeks.
Keywords: false negative